Metacognitive Scaffolding in Solving Numerical Literacy Problems in Secondary School (Universitas Pendidikan Indonesia Kampus Cibiru, 2023)
This research is an exploratory research with a qualitative approach that aims to describe the actual abilities, obstacles experienced by students, and the types of metacognitive scaffolding that need to be given to students in terms of improving numerical literacy problem-solving abilities. The validity of the data was obtained through in-depth interviews. The results of the study were obtained namely (1) Actual knowledge of subjects with moderate literacy (SS) ability improvement showed that they had understood the problem, but did not realize the need to include thick walls in calculating the volume of the pool. Meanwhile, subjects with increased low literacy (SR) skills did not understand the numerical literacy problems given and doubted the results of solving them. SR only writes down part of what is known and does not write down the thickness of the wall which is the part of the pool that must be known. This shows that there is a tendency for students to still be less accustomed to doing literacy, so that the information on the numerical literacy problem provided, cannot be understood properly. (2) The obstacles experienced by the SS were only because they did not realize the need to insert thick walls, so they experienced obstacles in each Step of Polya. While SR besides not understanding the problem of numerical literacy given, also not aware of what he writes. (3) The type of metacognitive scaffolding that needs to be given to SS and SR, shows that SR only needs a little help given, namely the type of monitoring and evaluating and the form of assistance is also categorised subtly, namely only in the form of asking. As for the metacognitive SR scaffolding that needs to be given, which is mostly in the form of directing and several times given the type of monitoring and the form of assistance is also categorized as rough, which is mostly in the form of directing and several times in the form of orders.